A novel configuration of solar integrated waste-to-energy incineration plant for multi-generational purpose: An effort for achieving maximum performance. (July 2022) - Khan, Muhammad Sajid; Huan, Qun; Yan, Mi; Ali, Mustajab; Noor, Obaid Ullah; Abid, Muhammad
Abstract: The efficiency of municipal solid waste to energy incineration plant is limited due to the higher amount of moisture content in the feedstock and huge heat loss. An innovative configuration is proposed in the present study to increase the performance of incineration plant. The new design consists of the integration of a solar thermal system with the incineration plant, so that the steam exiting the superheater of the municipal solid waste (MSW)incineration boiler is further heated by solar thermal system to increase its temperature and quality before entering the steam turbine. In addition, the flue gas is used to drive an iso-butane organic Rankine cycle to produce power that is utilized for hydrogen and freshwater production with the help of a proton exchange membrane electrolyzer and reverse osmosis system, respectively. Through a parametric analysis, the effect of major parameters on the performance of the proposed system is studied. The energy, exergy, and exergo-economic investigations are performed to access the system efficiencies, exergetic cost rates, sustainability index and total exergy destruction rate. The results show that the energy and exergy efficiencies of the integrated system are almost 21.34% and 16.64%, respectively, while thermal and exergy efficiencies of the MSW incineration plat are 37.35% and 35.22%, accordingly. The exergo-economic evaluation concludes that the exergy destruction rate of the system is 42965 kW with the rate of exergetic cost and total cost rate of 542 $/hr and 665 $/hr respectively. The sustainability index of the proposed system is calculated to be nearly 1.64, while fresh water and hydrogen production rates are 26.96 kg/s and 2.87 g/s, accordingly. In the end, the solar integrated waste-to-energy plant can provide multiple outputs simultaneously after adding the waste heat recovery system and the proposed system is theoretically feasible from the results of thermodynamic, economic, and environmental analysis. Graphical abstract: Image 1 Highlights: Innovative solar integrated WtE incineration plant with heat recovery system. Exhaust flue gasses utilized for hydrogen and freshwater production via ORC. System was evaluated by exergoeconomic analysis for detailed investigation. Sustainability index used for evaluating environmental performance. Single flow chart of exergy destruction rate, exergy cost and total cost rate.